Executive Committee Agenda 2015-04-23 - Academic Senate:::::::::
Agenda approved. Minutes of 4/9/16 – Approved. Chair Report. President Report. Direct Entry Masters in Nursing Discontinuance approved for Senate agenda. Reassigned Time request for '15 – '16 – postponed to next meeting. Human Development Revision approved for Senate agenda. FSAC & PDS Report. Early Childhood Education Certificate approved for the Senate consent calendar. Statewide Senator Report. Vice President of Student Affairs Report. EPC Report. SAC Report. CFA Report. Associated Students Report. Ex Com rep to the SEC report. Senate agenda approved. Good of the Order.